Aligning strategic and participatory approaches to agri‐environment scheme design and implementation to enhance nature recovery outcomes - D. J. Baker; C. Nye; R. Wheeler; C. Masquelier; A. Binner; K. J. Gaston; M. S. Heard; M. Lobley; D. Smith; I. M. D. Maclean (People and Nature)
Abstract Nature recovery requires the provisioning of resources in the right place and in sufficient quantities to support wildlife populations and improve ecological processes. Agri‐environment schemes (AES) have been a major mechanism for delivering environmental management across EU‐farmed landscapes, but measured benefits to nature are often negligible in large part due to a lack of strategic spatial targeting of management actions. As an example, AES in England are often delivered using a participatory strategy, typically at individual farm scale, with types of management agreements and uptake reflecting the business model and interests of each farm. However, this implementation model can result in poorly distributed conservation resources and, consequently, a failure to recover nature across larger scales, even if individual agreements are delivered well. Achieving effective, large‐scale nature recovery through AES requires aligning its implementation with spatially targeted approaches that prioritise specific conservation goals. We discuss the rationale for, and major barriers to, aligning AES design and implementation to these approaches. We then highlight how, through the framework of systematic conservation planning, both the strategic and participatory components of AES could be aligned better to enhance nature recovery outcomes. To ensure AES help achieve nature recovery goals, clear and measurable targets must be set with the type and spatial configuration of actions designed to enable meeting targets. Strategic spatial targeting must also be carried out with the implementation phase in mind, accounting for socio‐economic opportunities and barriers to engagement and acknowledging that uncertainties around farm‐scale implementation mean plans must be adaptable. Participatory approaches for AES design and implementation that support the delivery of spatially targeted management actions are required, most notably by facilitating collaboration or cooperation across farm holdings. For AES to contribute effectively to nature recovery goals, aligning strategic and participatory approaches in its design and implementation is crucial. This requires uniting knowledge across disciplines and cultures and ensuring that information is shared to support progressive refinement of scheme design and guidance towards achieving overall nature recovery goals. Read the free Plain Language Summary for this article on the Journal blog.